Catalytic Arylation Methods. From the Academic Lab to Industrial Processes. Von Anthony J. Burke und Carolina Silva Marques. (27th October 2015) - Hapke, Marko
Abstract : Wiley‐VCH, Weinheim, 2014. 528 S., geb., 162.00 €.—ISBN 978‐3527335183